Dietary supplementation with aromatic amino acids decreased triglycerides and alleviated hepatic steatosis by stimulating bile acid synthesis in mice. Issue 1 (10th December 2020) - Ma, Qingquan; Chen, Jiayi; Zhou, Xinbo; Hu, Linlin; Sun, Yuchen; Wang, Zhishen; Yue, Zhiyuan; Shan, Anshan
Abstract : Increased aromatic amino acids intake improved lipid metabolism by stimulating bile acid synthesis. Abstract : Emerging evidence shows that amino acids can modulate lipid metabolism. Aromatic amino acids (AAAs) serve as important precursors of several neurotransmitters and metabolic regulators that play a vital role in regulating nutrient metabolism. But whether AAAs have a lipid-lowering function remains unknown. Here mice were fed amino acid-defined diets containing AAAs at 1.82% and 3.64% for 3 weeks. We demonstrated that double AAA intake significantly decreased the serum and hepatic triglycerides and serum low-density lipoprotein cholesterol, but increased the high-density lipoprotein cholesterol as well as insulin tolerance. Combined metabolomic and transcriptomic analysis showed that the hepatic acidic pathway of bile acid synthesis was responsible for the improvement in lipid metabolism by AAA treatment. This study suggests that AAAs have the potential to ameliorate steatosis and provides a new alternative to improve lipid metabolism.